Peripheral artery disease in patients with acute coronary syndrome without ST-segment elevation: impact on therapy and prognosis. (3rd May 2023) - Carias, M; Paralta, M; Almeida, A; Claudio, F; Rocha, R; Picarra, B; Bento, A; Trinca, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Peripheral artery disease (PAD) is an important co-morbidity in non-ST-segment elevation acute coronary syndromes (NSTEMI), and its presence may affect the therapeutic approach and prognosis of these patients. Purpose: To assess the impact of PAD presence on therapeutic approach, clinical outcome, and in-hospital and 1-year mortality in patients with NSTEMI. Methods: We studied 7248 patients with NSTEMI included in a national multicenter registry. We considered 2 groups: patients with PAD and patients without PAD. Demographic variables, CV risk factors, inpatient therapy, left ventricular function (LVF), coronary angiography and revascularization strategy performed were recorded. The following in-hospital adverse events (AE) were defined: death, re-infarction, stroke, heart failure (HF), cardiogenic shock (CC), major bleeding (MH), need for blood transfusion (BT). Length of stay (IT) and in-hospital and 1-year mortality were evaluated. Multivariate analysis was performed to assess whether the presence of PAD is a predictor of HAS and/or 1-year mortality. Results: The presence of PAD was 7.3% (526 patients). These patients were older (70±11 vs 67±13 years, p<0.001), higher prevalence of males (82.1 vs 70.7%, p<0.001), arterial hypertension (87.4 vs 74.1%, p<0.001), diabetes mellitus ( 55.3 vs 32.3%, p<0.001), dyslipidemia (76 vs 61.9%, p<0.001), previous AMI (48.4 vs 24.6%, p<0.001), previous PCI (28.4 vs 17.5%, p<0.001), CABG ( 20.0 vs 6.5%, p<0.001), stroke (25.4 vs 7.5%, p<0.001) and chronic renal failure (22.9 vs 6.3%, p<0.001). Patients with PAD: evolved more frequently in Killip≥II (26.0 vs 13.9%, p<0.001), with LV dysfunction (LVF<50%: 42.7 vs 28.3%, p<0.001) and the need for non-invasive ventilation (3 vs 1.7%, p=0.019). Patients with PAD were less frequently medicated with beta-blockers (75 vs 87.5%, p<0.001) and more frequently with diuretics (47.3 vs 26.6%, p<0.001). Patients with PAD underwent fewer coronary angiograms (69.8 vs 85.6%, p<0.002), but the femoral approach was more used (35.2 vs 21.4%) and had more multivessel disease (76.7 vs 52.4%, p<0.001). Patients with PAD had a longer in-hospital stay duration (median 7 vs 5 days, p<0.001), higher incidence of re-AMI (3.1 vs 1.4%, p=0.003), HF (26.7 vs 12.4%, p=0.002), CC (3.2 vs 1.8%, p=0.016), MH (2.3 vs 1.1%, p=0.001) and BT (4.6 vs 1.6%, p<0.001), but not stroke. In-hospital mortality was higher (4 vs 2%, p=0.003) as well as 1-year mortality (16.2 vs 6.2%, p<0.001). By multivariate analysis, PAD was an independent predictor of 1-year mortality (OR=1.57, 95% CI [1.04-2.58], p=0.032), but not of AE. Conclusion: The presence of PAD affects the therapy and revascularization strategy in patients with NSTEMI, being associated with higher in-hospital morbidity and mortality. This co-morbidity constitutes an independent predictor of death at 1 year.